Pyramidal II to basal transformation of ⟨c + a⟩ edge dislocations in Mg-Y alloys. (October 2018) - Ahmad, Rasool; Wu, Zhaoxuan; Groh, Sébastien; Curtin, W.A.
Abstract: Transitions of pyramidal ⟨ c + a ⟩ dislocations to sessile structures contribute to poor ductility in pure Mg. Mg-3 wt% Rare Earth (RE) alloys have good ductility, possibly due to ⟨ c + a ⟩ dislocation stabilization upon addition of RE solutes. Here, ⟨ c + a ⟩ stability is investigated in a model Mg-3 at.%Y random solid solution alloy using molecular dynamics simulations. Favorable fluctuations of Y solutes lower all dislocation energies and have no appreciable effects on the transition mechanism, energy barrier, or time. Enhanced ⟨ c + a ⟩ activity and improved ductility in Mg-3 wt%RE alloys are thus not likely associated with solute-stabilization of pyramidal ⟨ c + a ⟩ dislocations. Graphical Abstract: